2010
DOI: 10.1002/bjs.7002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for portal venous thrombosis after splenectomy in patients with cirrhosis and portal hypertension

Abstract: Large splenic vein diameter and low white cell count are independent risk factors for PVT after splenectomy in patients with cirrhosis and portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 33 publications
7
82
1
Order By: Relevance
“…Reduced portal flow velocity seems to be the most important predictive variable for PVT development in patients with cirrhosis [37][38][39] . Amitrano et al [38] suggested that portal blood stasis in patients with cirrhosis is the main change favoring thrombosis, even in the presence of other local, systemic, congenital and acquired factors.…”
Section: Etiology Of Pvt In Cirrhosismentioning
confidence: 97%
See 3 more Smart Citations
“…Reduced portal flow velocity seems to be the most important predictive variable for PVT development in patients with cirrhosis [37][38][39] . Amitrano et al [38] suggested that portal blood stasis in patients with cirrhosis is the main change favoring thrombosis, even in the presence of other local, systemic, congenital and acquired factors.…”
Section: Etiology Of Pvt In Cirrhosismentioning
confidence: 97%
“…Amitrano et al [38] suggested that portal blood stasis in patients with cirrhosis is the main change favoring thrombosis, even in the presence of other local, systemic, congenital and acquired factors. Kinjo et al [39] performed Doppler ultrasonographic examinations after splenectomy in patients with cirrhosis and showed that portal venous flow was dramatically decreased by 49.2% in the PVT group but only by 6.6% in the non-PVT group.…”
Section: Etiology Of Pvt In Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of PVST mainly focused on myelodysplastic syndromes (8)(9)(10), hemolytic anemia (8,9), spleen tumors (8), and traumatic splenic rupture (9). In recent years, it has been found that patients with cirrhosis and portal hypertension also have high risks of developing PVST after splenectomy (11). To date, the mechanism underlying PVST formation in these patients is still unclear, and the prophylactic application of anticoagulants is controversial because of the concerns about the risk of inducing bleeding (12,13).…”
Section: Introductionmentioning
confidence: 99%